Identification Of Gastrointestinal Protozoa Of Swine (Sus sp.) In Surabaya Slaughterhouse In Dry Season - Amalia Rosydinasari Rosydinasari; Nunuk Dyah Retno Lastuti; Ira Sari Yudaniayanti; Mufasirin (Journal of Parasite Science (JoPS), 2023)
Surabaya slaughterhouse provides pork cuts from several swine farms. Prior to slaughter, the swine were placed in a temporary pen which allows the transmission of gastrointestinal protozoa to fellow swine and to humans at the Surabaya slaughterhouse. This research was conducted to identify gastrointestinal protozoa of swine that slaughtered in Surabaya slaughterhouse. Total of 100 fecal samples was observed using native method, sedimentation method, Fulleborne floating method and Ziehl neelsen method. Based on the results, there were 47 samples positive. The protozoa found included Balantidium sp. with 46% prevalence, Eimeria sp. / Isospora sp. with 32% prevalence, Entamoeba sp. with 24% prevalence, and Blastocystis sp.with 12% prevalence.